Single-cell RNA sequencing reveals the cellular and molecular changes that contribute to the progression of lung adenocarcinoma - Liu, Bing; Wang, Chen; Fang, Zhanjie; Bai, Jing; Qian, Ying; Ma, Yuanyuan; Ruan, Xiuyan; Yan, Shi; Li, Shaolei; Wang, Yaqi; Dong, Bin; Yang, Xin; et al. (Frontiers in Cell and Developmental Biology, 2022)
Pure ground glass nodules (GGNs) and solid nodules (SNs) represent early and relatively late stage of lung adenocarcinoma (LUAD) in radiology, respectively. The cellular and molecular characteristics of pure GGNs and SNs have not been comprehensively elucidated. Additionally, the mechanism driving the progression of lung adenocarcinoma from pure GGN to SN in radiology is also elusive. In this study, by analyzing single-cell transcriptomic profiles of 76,762 cells from four pure GGNs, four SNs and four normal tissues, we found that anti-tumor immunity mediated by NK and CD8+T cells gradually weakened with the progression of LUAD and humoral immunity mediated by plasma B cells were more active in SNs. Additionally, the proliferation ability of some special epithelial cell increased during the progression process from pure GGN to SN. Furthermore, stromal cells and M2 macrophages could assist the progression of LUAD. Through comprehensive analyses, we revealed dynamic changes in cellular components and intercellular interactions during the progression of LUAD. These findings could facilitate our understanding of LUAD and discovery of novel therapeutic targets.